Analisis Permintaan Konsumen Rumah Tangga terhadap Minyak Goreng Curah di Kota Denpasar - I MADE ADI DWIRANA PUTRA; KETUT BUDI SUSRUSA; NI WAYAN PUTU ARTINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Analysis Of Household Consumer Demand On Bulk Cooking Oil in Denpasar CityNowadays cooking oil is sold in two forms; one is referred to as bulk cooking oil‘minyak goreng curah’ and the other is referred to as packaged cooking oil ‘minyakdalam kemasan’ with a particular trademark. However, the consumers in Denpasar stillprefer the bulk cooking oil to the packaged cooking oil. This present study was intendedto identify the factors contributing to the demand for the bulk cooking oil and theelasticity of the demand in Denpasar City. The study was conducted at Satrya Market,Sanglah Market, Kreneng Market, and Badung Market, which were all purposivelydetermined. The samples were taken using the accidental sampling technique, totaling40 and were purposively determined. This research uses Cobb-Douglas function withtransformed data. The independent variables were X1 (the price of the bulk cooking oil),X2 (the price of the packaged cooking oil), X3 (the price of chicken), X4 (the number offamily members), and X5 (the family income). The result of the model was as followslnY = -5,876 – 2.184lnX1* + 3.588lnX2* - 0.332lnX3 + 0.311lnX4* + 0.244lnX5*. Thefactors which contributed to the demand for the bulk cooking oil were its price, the priceof the packaged cooking oil, the price of chicken, the number of family members, andthe family income. The price of the bulk cooking oil showed elasticity. The crosselasticity showed that the packaged cooking oil was a substitution commodity and thatchicken was a complementary commodity. The income elasticity showed that the bulkcooking oil was an inferior commodity.